RELATIONSHIP BETWEEN BUSINESS FAILURE AND INTEREST IN TURKEY (Third Sector Social Economic Review, 2021)
It is seen that the concept of business failure has been widely studied in developed and developing countries in recent years. While studies generally focus on the internal causes of business failure, the necessity of examining external causes at least as much as internal causes has emerged. In this context, the number of business closures in Turkey in the study and interest rate relationships were investigated using Leveraged Bootstrap Todo-Yamamoto test period of February 2020 through January 2010 data. According to the results of the causality test, a unilateral causality relationship was determined from the interest rate to the number of businesses closed.
Keywords: Business Failure; Interest; Econometric Analysis